Nitrogen Flow in Diazotrophic Cyanobacterium Aphanizomenon flos-aquae Is Altered by Cyanophage Infection - Kuznecova, Jolita; Šulčius, Sigitas; Vogts, Angela; Voss, Maren; Jürgens, Klaus; Šimoliūnas, Eugenijus (Frontiers in Microbiology, 2020)
Viruses can significantly influence cyanobacteria population dynamics and activity, and through this the biogeochemical cycling of major nutrients. However, surprisingly little attention has been given to understand how viral infections alter the ability of diazotrophic cyanobacteria for atmospheric nitrogen fixation and its release to the environment. This study addressed the importance of cyanophages for net 15N2 assimilation rate, expression of nitrogenase reductase gene (nifH) and changes in nitrogen enrichment (15N/14N) in the diazotrophic cyanobacterium Aphanizomenon flos-aquae during infection by the cyanophage vB_AphaS-CL131. We found that while the growth of A. flos-aquae was inhibited by cyanophage addition (decreased from 0.02 h–1 to 0.002 h–1), there were no significant differences in nitrogen fixation rates (control: 22.7 × 10–7 nmol N heterocyte–1; infected: 23.9 × 10–7 nmol N heterocyte–1) and nifH expression level (control: 0.6–1.6 transcripts heterocyte–1; infected: 0.7–1.1 transcripts heterocyte–1) between the infected and control A. flos-aquae cultures. This implies that cyanophage genome replication and progeny production within the vegetative cells does not interfere with the N2 fixation reactions in the heterocytes of these cyanobacteria. However, higher 15N enrichment at the poles of heterocytes of the infected A. flos-aquae, revealed by NanoSIMS analysis indicates the accumulation of fixed nitrogen in response to cyanophage addition. This suggests reduced nitrogen transport to vegetative cells and the alterations in the flow of fixed nitrogen within the filaments. In addition, we found that cyanophage lysis resulted in a substantial release of ammonium into culture medium. Cyanophage infection seems to substantially redirect N flow from cyanobacterial biomass to the production of N storage compounds and N release.